Some Identities on Laguerre Polynomials in Connection with Bernoulli and Euler Numbers - Dae San Kim; Taekyun Kim; Dmitry V. Dolgy (Discrete Dynamics in Nature and Society)
We study some interesting identities and properties of Laguerre polynomials in connection with Bernoulli and Euler numbers. These identities are derived from the orthogonality of Laguerre polynomials with respect to inner product ∫⟨𝑓,𝑔⟩=∞0𝑒−𝑥2𝑓(𝑥)𝑔(𝑥)𝑑𝑥.